(untitled) (Journal of Chemical Engineering, 2014)
The purpose of the work is to investigate the scenario of waste water treatment in pharmaceutical industries in Bangladesh and find some advanced steps to add in the existing ETP with economic considerations. For this, a renowned pharmaceutical industry in Bangladesh has been chosen that represents the feature of ETP in Bangladesh. Generally industries, including pharmaceuticals, discharge their waste water to the environment after treatment; the objective is to show some beneficial ways to use/reuse the treated water, applicable for the pharmaceutical industries in Bangladesh. Sample has been provided by ACI Pharmaceuticals Ltd. and different parameters of their supplied samples (both from inlet and outlet) have been measured to check whether they suit with the present standards of drinking water and/or other standards of industrial discharged water in context of Bangladesh. From the experiment it is found that the values of the different parameters of the treated water of the chosen industry can be considered to be favorable in comparison with the present standards of waste water regulations in Bangladesh. The present investigation also shows that if an ion exchange unit or membrane separation technology is incorporated after filtration, the waste water can be made potable after treatment by implementing some advanced technology DOI: http://dx.doi.org/10.3329/jce.v27i2.17801 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, December 2012: 46-49